Labrador, aerial view of coastline between Kangalaksiorvik Fjord and Nachvak Fjord - Forbes, Alexander, 1882-1965 (1931)
(Series 12) Similar to Series 11, but flight a little further inland. Inshore east coast flight from Kangalaksiorvik to Nachvak. Camera facing left front to line of flight. Grayscale